Anti-IgLON5 Disease – The Current State of Knowledge and Further Perspectives - Madetko, Natalia; Marzec, Weronika; Kowalska, Agata; Przewodowska, Dominika; Alster, Piotr; Koziorowski, Dariusz (Frontiers in Immunology, 2022)
Anti-IgLON5 disease is a relatively new neurological entity with the first cases reported in 2014. So far, less than 70 articles on this topic have been published. Due to its unspecific symptomatology, diverse progression, novelty and ambiguous character, it remains a difficulty for both clinical practitioners and scientists. The aim of this review is to summarize the current knowledge concerning anti-IgLON5 disease; mechanisms underlying its cause, symptomatology, clinical progression, differential diagnosis and treatment, which could be helpful in clinical practice and future research.